Hierarchically Macroporous Cryogels of Polyisobutylene and Silica Nanoparticles - TUNCABOYLU, DENIZ CEYLAN; Tuncaboylu, Deniz C.; Okay, Oğuz (My University, 2010)
Organic inorganic hybrid materials attract particular interest because of their excellent mechanical properties. Here, we report the synthesis of hybrid cryogels consisting of interpenetrated polyisobutylene and silica networks. The gels were prepared by cross-linking of butyl rubber in cyclohexane containing silica nanoparticles using sulfur monochloride (S2Cl2) as a cross-linking agent. The microstructure of the hybrid networks formed at subzero temperatures exhibits two generations of pores: 10(1) mu m sized large pores due to the cyclohexane crystals acting as a template during gelation and, 10(-1)-10(0) mu m sized small pores between the aggregates of the nanoparticles. The nanoparticles in hybrid cryogels accumulate within the large pores where cyclohexane crystals originally resided. Compared to the organogel networks with an elastic modulus of a few kPa, hybrid networks exhibit a modulus of elasticity around 300 kPa. Hybrid cryogels can be converted into organic cryogels by dissolving the silica component in aqueous hydrofluoric acid, while removing the polymer component by calcination results in porous silica networks with 10(-1) mu m sized pores.